Animal models of congenital zika syndrome provide mechanistic insight into viral pathogenesis during pregnancy - Narasimhan, Harish; Chudnovets, Anna; Burd, Irina; Pekosz, Andrew; Klein, Sabra L. (PLoS neglected tropical diseases, 2020)
In utero Zika virus (ZIKV; family Flaviviridae) infection causes a distinct pattern of birth defects and disabilities in the developing fetus and neonate that has been termed congenital zika syndrome (CZS). Over 8,000 children were affected by the 2016 to 2017 ZIKV outbreak in the Americas, many of whom developed CZS as a result of in utero exposure. To date, there is no consensus about how ZIKV causes CZS; animal models, however, are providing mechanistic insights. Using nonhuman primates, immunocompromised mice, immunocompetent mice, and other animal models (e.g., pigs, sheep, guinea pigs, and hamsters), studies are showing that maternal immunological responses, placental infection and inflammation, as well as viral genetic factors play significant roles in predicting the downstream consequences of in utero ZIKV infection on the development of CZS in offspring. There are thousands of children suffering from adverse consequences of CZS. Therefore, the animal models developed to study ZIKV-induced adverse outcomes in offspring could provide mechanistic insights into how other viruses, including influenza and hepatitis C viruses, impact placental viability and fetal growth to cause long-term adverse outcomes in an effort to identify therapeutic treatments.